Multibeam bathymetry raw data (Kongsberg EM710 entire dataset) of RV HEINCKE during cruise HE588 - Lasse Sander; Jasper Hoffmann; Alexander Bartholomä; Mara Luisa Hochstein; Frieda Müller (PANGAEA, 2024)
Raw multibeam bathymetry data from the Kongsberg EM710 was acquired during the RV Heincke cruise HE588 in the German Bight. The data was generally acquired during calm seas in water depths between 15 and 50 m. Primarily four different regions were surveyed (Borkumer Reef Ground, Sylt Outer Reef, Sylt and Amrum Bank). In some areas, the data is comprehensive and overlapping swaths creating a continuous bathymetry were archived. In other areas the data was acquired complementary to sidescan sonar surveys and individual tracks do not overlap. Data are unprocessed and therefore may contain some incorrect depth measurements (artifacts) without further processing. No tide variations are applied. Sound velocity profiles were acquired regularly. Overall, it appears that the data quality is rather good. The gridded data showed relatively few obstacles.